Potential for Negative Emissions by Carbon Capture and Storage From a Novel Electric Plasma Calcination Process for Pulp and Paper Mills - Svensson, Elin; Wiertzema, Holger; Harvey, Simon (Frontiers in Climate, 2021)
The pulp and paper industry has a high potential to contribute to negative emissions through carbon capture and storage (CCS) applied to existing processes. However, there is a need to investigate how CCS solutions also can be combined with implementation of other emerging technologies in pulp and paper mills. This paper investigates the integration of a novel calcination process in two kraft mills and evaluates its potential combination with capture and storage of CO2 from the calcination plant. The alternative calcination process uses electric gas-plasma technology combined with steam slaking and allows replacing the conventional fuel-driven lime kilns with a process driven by electricity. The novel calcination process generates a pure, biogenic, CO2 stream, which provides an opportunity to achieve negative emissions at relatively lower costs. The potential reduction of greenhouse gas emissions when replacing the lime kiln with the plasma calcination concept depends strongly on the emissions intensity of grid electricity, and on whether fossil fuel or biomass was used as a fuel in the lime kiln. If fossil fuel is replaced and electricity is associated with very low emissions, avoided CO2 emissions reach approximately 50 kt/a for the smaller mill investigated in the paper (ca 400 kt pulp per year) and almost 100 kt/a for the larger mill (ca 700 kt pulp per year). Further emission reductions could then be achieved through CCS from the electrified calcination process, with capture potentials for the two mills of 95 kt/a and 164 kt/a respectively, and capture and storage costs estimated to 36–60 EUR/tCO2.